Pengaruh Pendekatan Kontekstual Terhadap Pemahaman Konsep Pada Materi Hukum Newton 1 di Kelas VIII SMP Negeri 04 SATAP Entikong - Bahri, Samsul; Budhiarti, Yuli; Noviyah, Noviyah (QUANTUM: Jurnal Pembelajaran IPA dan Aplikasinya, 2024)
Research problem is a lack of understanding of the concepts in Newton's I Law material and a lack of the right approach so that students quickly get bored and are lazy to pay attention in the physics learning process.The aim of the research is to find out whether the contextual approach influences students' conceptual understanding of Newton's I law material. Pre-Experimental experimental method with a quantitative approach one group pretest posttest design.Research population consisted of 13 class VIII students at SMP Negeri 04 SATAP Entikong. Data collection technique uses pretest and posttest test sheets by paying attention to four indicators of concept understanding.Data analysis using normality test and Wilcoxon test. Based on the normality test results, X2 count X2 table with a pretest value of 24.417 9.488 and a posttest value of -74.983 9.488.The results of research using the percentage categories of the four indicators of students' conceptual understanding show that the first indicator is 69% moderate, the second 92% high, the third 84% high, and the fourth 92% high.Based on the Wilcoxon test, the W count is 91 W table 17.So it can be concluded that Ha is accepted and Ho is rejected, meaning that there is an influence of the contextual approach on understanding concepts in Newton's I law material.Keywords:Contextual Approach, Understanding Concepts, Newton's I Laws.